Challenges and Benefits of Repurposing Products for Use during a Radiation Public Health Emergency: Lessons Learned from Biological Threats and other Disease Treatments - DiCarlo, Andrea L; Cassatt, David R; Dowling, William E; Esker, John L; Hewitt, Judith A; Selivanova, Oxana; Williams, Mark S; Price, Paul W (Radiation research, 2018)
The risk of a radiological or nuclear public health emergency is a major growing concern of the U.S. government. To address a potential incident and ensure that the government is prepared to respond to any subsequent civilian or military casualties, the U.S. Department of Health and Human Services and the Department of Defense have been charged with the development of medical countermeasures (MCMs) to treat the acute and delayed injuries that can result from radiation exposure. Because of the limited budgets in research and development and the high costs associated with bring promising approaches from the bench through advanced product development activities, and ultimately, to regulatory approval, the U.S. government places a priority on repurposing products for which there already exists relevant safety and other important information concerning their use in humans. Generating human data can be a costly and time-consuming process; therefore, the U.S. government has interest in drugs for which such relevant information has been established (e.g., products for another indication), and in determining if they could be repurposed for use as MCMs to treat radiation injuries as well as chemical and biological insults. To explore these possibilities, the National Institute of Allergy and Infectious Diseases (NIAID) convened a workshop including U.S. government, industry and academic subject matter experts, to discuss the challenges and benefits of repurposing products for a radiation indication. Topics covered included a discussion of U.S. government efforts (e.g. funding, stockpiling and making products available for study), as well unique regulatory and other challenges faced when repurposing patent protected or generic drugs. Other discussions involved lessons learned from industry on repurposing pre-license, pipeline products within drug development portfolios. This report reviews the information presented, as well as an overview of discussions from the meeting.